Deconstructing Masculinity in Translation: How Female Characters Are Portrayed in Story Weaver’s Children’s Literature - Diana Hardiyanti; Riana Eka Budiastuti; Lilis Setyowati; Budi Tri Santoso (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2026)
Abstract Background: Masculinity is commonly associated with men, which leads children’s stories to reinforce narrow gender stereotypes. As these stories are translated and circulated across cultures, translation choices may either maintain or reshape such representations. However, the translation of female masculinity in children’s stories remains underexplored, particularly through transitivity perspective. This study examines StoryWeaver translations portraying female masculinity to analyze how masculinity is identified using Systemic Functional Linguistics (SFL), how it is translated, and how translation techniques affect its representation. Methodology: This study uses a qualitative descriptive approach with five purposively selected StoryWeaver stories. Credibility was ensured through data source triangulation via document analysis and methodological triangulation through focus group discussion (FGD). SFL was used to identify constructions of masculinity, while translation techniques analysis examined how masculinity was translated from the source to the target language. A double case study design treated the five stories as individual cases for cross-case comparison across different authors and translators. Data were analysed using Spradley’s ethnographic procedures. Findings: Five forms of masculinity were identified, realized through material, mental, relational, behavioral, and existential processes, revealing how female masculinity is linguistically constructed in children’s narratives. Established equivalents dominated the translations, while deletion also influenced the representation of masculinity. Conclusion: Translation techniques play a role in shaping how female masculinity is represented, with established equivalents tending to maintain meaning and deletion leading to shifts in representation. Originality: The study addresses the limited research on translating female masculinity in children’s literature and shows how translation choices shape gender meanings for young readers across languages and cultures.